2002
DOI: 10.1053/rmed.2001.1292
|View full text |Cite
|
Sign up to set email alerts
|

Survey of patients' views of domiciliary nebuliser treatment for chronic lung disease

Abstract: There is some controversy amongst respiratory physicians over the value of domiciliary nebuliser use for chronic lung conditions. Most recommendations for assessment of suitability for this form of treatment rely upon response to lung function tests and reported improvements in exercise ability. Relatively little emphasis has been placed upon the patient view of this therapy. This survey examined the subjective views of patients receiving domiciliary nebulisers regarding this treatment. A postal questionnaire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 16 publications
1
33
0
Order By: Relevance
“…For example, some patients require nebulized therapy due to comorbidities or functional impairment, while others prefer the nebulized route of administration for these medications because they feel they are more effective. 5 The GOLD and AMDA guidelines recommend a stepwise approach to therapy for patients with COPD.…”
Section: ■■ Methodsmentioning
confidence: 99%
“…For example, some patients require nebulized therapy due to comorbidities or functional impairment, while others prefer the nebulized route of administration for these medications because they feel they are more effective. 5 The GOLD and AMDA guidelines recommend a stepwise approach to therapy for patients with COPD.…”
Section: ■■ Methodsmentioning
confidence: 99%
“…Eleven studies examined the aspects of operation of inhalation devices and described the frequency and range of problems experienced by COPD patients when using their inhalation devices (Table 2). These studies were mostly based in outpatient clinics (N=11) (Lenney et al, 2000;Hesselink et al, 2001;George et al, 2005;Khassawneh et al, 2008;De Moraes Souza et al, 2009;Rootmensen et al, 2010;Melani et al, 2011;Agh et al, 2011 ;Cecere et al, 2012;Huetsch et al, 2012;Khdour et al, 2012), and patients' home (N=5) (Melani et al, 2001;Barta et al, 2002;Boyter and Carter, 2005;George et al, 2006;Sestini et al, 2006). Others were based in community pharmacies (N=3) (Hämmerlein et al, 2011;Mehuys et al, 2010;Trivedi et al, 2012).…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…Most of these studies were conducted in Europe, especially the UK (N=6) (Lenney et al, 2000;Barta et al, 2002;Ho et al, 2004;Boyter and Carter, 2005;Wilson et al, 2007;Khdour et al, 2012), followed by Italy (N=3) (Melani et al, 2001;Sestini et al, 2006;Melani et al, 2011), and the Netherlands (N=1) (Rootmensen et al, 2010), Belgium (N=1) (Mehuys et al, 2010), Hungary (N=1) (Agh et al, 2011), France (N=1) (Hesselink et al, 2001), Germany (N=1) (Hämmerlein et al, 2011), the USA (N=3) (Cecere et al, 2012;Huetsch et al, 2012;Trivedi et al, 2012), Australia (N=2) (George et al, 2005;George et al, 2006), Brazil (N=1) (De Moraes Souza et al, 2009) and Jordan (N=1) (Khassawneh et al, 2008).…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, some elderly patients prefer nebulizer, not only for acute severe episodes of bronchospasm, but for regular long-term home use. [2][3][4] An exhaustive literature review revealed that there is a paucity of randomized controlled studies on nebulization of corticosteroids, as most research trials have employed metereddose inhalers. 1 Additionally, although in vitro experiments can be a surrogate for in vivo investigation of respiratory drug delivery, 5 extensive information about nebulized corticosteroids from in vitro studies is still not available.…”
Section: Introductionmentioning
confidence: 99%